Effect of Combination Kiambang (Salvinia molesta) and Zeolite on Consentration of Heavy Metal Cadmium (Cd). - Siti Nurafifah; Boedi Setya Rahardja; Abdul Manan (Universitas Airlangga, 2018)
Water is the most important requirement for all organisms, either to humans, plants, animals, and microorganisms. It was caused water function in the growth and survival organisms. Aquaculture is an activity to maintain, raise, and/or breeding fish and harvest their products in a controlled environment. Cultivation was done in a sustainable manner for the benefit.Pollution in water can be caused death of fish is heavy metal cadmium (Cd) pollution. Processing of heavy metal contaminated water is the most simple and low cost is a biological treatment with kariba weed (Salvinia molesta). But the effect of kariba weed to the decline of heavy metal cadmium is not significantly reduced, so that needs to be combined with the zeolite so that the heavy metal cadmium decline more significantly. This reseacrh to determine the effect of the combination kariba weed (Salvinia molesta) and zeolite to the decline of the heavy metal cadmium (Cd). This reseacrh uses a completely randomized design (CRD) with four treatments performed five repetitions, treatment A using 0 g kariba weed and 150 g of zeolite, Treatment B using 50 g kariba weed and 100 g of zeolite, Treatment C using 100 g kariba weed and 50 g of zeolite and treatment D using 150 g kariba weed and 0 g zeolite. The result on this research analize by ANOVA statistical test (Analisis of Variance) to know there was the different between treatments, afterwards, continued by space doubled test Duncan. The result showed combination kariba weed (Salvinia molesta) and zeolite significant effect on decreasing the concentration of heavy metal cadmium (Cd) (F count > F Tabel 0.05). It is evident in this research, and only had one week treated water cadmium (Cd) of 1 ppm concentrations is fall. The averages treatment on decreasing concentration heavy metal cadmium (Cd) was treatment A 98,7%, tretment B 97,1%, treatment C 97,2 % and treatment D 95,8%.